Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-12-26T13:53:55+01:00
Soit A= 4x²-9-(2x+3)(x-1)

Développer et réduire A

A= 4x²-9-(2x+3)(x-1)
  =4x²-9-(2x²+3x-2x-3)
  =4x²-9-2x²-x+3
  =2x²-x-6

Factoriser 4x²-9
4x²-9=(2x-3)(2x+3)

En déduire une factorisation de A
A=(2x-3)(2x+3)-(2x+3)(x-1)
  =(2x+3)(2x-3-x+1)
  =(2x+3)(x-2)

pour x= 3/2 A=0
pour x= -4
A=30


2013-12-26T13:56:47+01:00
1)A=4x²-9-(2x+3)(x-1)
A=4x²-9-(2x²-2x+3x-3)
A=4x²-9-2x²+2x-3x+3
A=2x²-x-6
2)
a) 4x²-9=(2x-3)(2x+3)
b) A=(2x-3)(2x+3)-(2x+3)(x-1)
A=(2x+3)(2x-3)-(x-1)
A=(2x+3)(2x-3-x+1)
A=(2x+3)(x-2)
3)
x=3/2
(3+3)(3/2-2)
(9)(3/2-4/2)
9(-1/2)=-4,5
x=-4
(-8+3)(-4-2)
(-5)(-6)=30
x=